Identification of Characteristic Flavor Compounds and Quality Evaluation of Butyriboletus roseoflavus from Different Regions in Yunnan - Ling Song; Qiming Zhao; Xuebin Shao; Xiangqian Lv; Juan Lu; Ruiping Luo; Yurong Liu; Xing Zhou; Qiang Li; Mingying Gui (Foods)
Butyriboletus roseoflavus is a rare wild edible mushroom. Yet, the relationship between its chemical composition and quality, as well as the influence of geographic origin on its flavor profile, remains unclear. In this study, ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) and headspace solid-phase microextraction coupled with gas chromatography–mass spectrometry (HS-SPME-GC-MS) were used to investigate flavor differences and influencing factors among samples from different regions. Seventeen key volatile compounds (OAV > 1) were identified, with α-pinene, styrene, octanal, 1,3,5-trithiane, and 2,4-undecadienal being the primary aroma contributors. Six characteristic taste-active compounds (TAV > 1) were detected, among which Glu, Ala, and His played dominant roles. Differential metabolites were mainly enriched in nucleotides and their derivatives, suggesting their importance in environmental adaptation and quality formation. Correlation analysis revealed that the abundance of key metabolites was closely related to geographic origin: temperature, humidity, light intensity, and CO2 concentration mainly influenced aroma variation, while taste differences were associated with soil electrical conductivity and microclimatic changes mediated by altitude. These findings provide a comprehensive understanding of the flavor characteristics of B. roseoflavus and offer a theoretical basis for its future processing and utilization.